Krüppel-like factor 2: a central regulator of B cell differentiation and plasma cell homing - Wittner, Jens; Schuh, Wolfgang (Frontiers in Immunology, 2023)
The development of B cells, their activation and terminal differentiation into antibody-producing plasma cells are characterized by alternating phases of proliferation and quiescence that are controlled by complex transcriptional networks. The spatial and anatomical organization of B cells and plasma cells inside lymphoid organs as well as their migration within lymphoid structures and between organs are prerequisites for the generation and the maintenance of humoral immune responses. Transcription factors of the Krüppel-like family are critical regulators of immune cell differentiation, activation, and migration. Here, we discuss the functional relevance of Krüppel-like factor 2 (KLF2) for B cell development, B cell activation, plasma cell formation and maintenance. We elaborate on KLF2-mediated regulation of B cell and plasmablast migration in the context of immune responses. Moreover, we describe the importance of KLF2 for the onset and the progression of B cell-related diseases and malignancies.